Adhesive-Enhanced Sternal Closure: Feasibility and Safety of Late Sternal Reentry - Aaron J. Spooner; Holly E. M. Mewhort; Lisa M. DiFrancesco; Paul W. M. Fedak (Case Reports in Surgery)
This clinical case report describes sternal reentry performed years after adhesive-enhanced sternal closure using Kryptonite bone cement. This report provides novel data on the late effects of this innovation. We observed that sternal reentry is feasible and safe. The adhesive did not weaken from biodegradation over a period of several years. There was no evidence of adherence to adjacent soft tissues or other nonbony deep mediastinal structures. Surgeons who receive patients who require redoing cardiac surgery after adhesive-enhanced closure with Kryptonite can be reassured that sternal reentry is safe and feasible.